PENGARUH INTENSITAS MENGUNGGAH VIDEO TERHADAP EKSISTENSI DIRI ANGGOTA KOMUNITAS PKUVIDGRAM (PEKANBARU VIDEO INSTAGRAM) - Indah Permata Sari; Rumyeni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Developments in technology, communications, and information associated with a significant dependence on the social media audience that social media becomes a necessity that must be accessed every day. One of the popular social media is instagram, namely an application for sharing photos and short videos that are 15 seconds. Instagram is very easy for audiences to share videos in a fast way so that the audience can upload videos every day. Dependency Theory to explain the nature of one's dependence on a medium in this case is social media audiences can demonstrate the existence themselves through video upload. The purpose of this study is to determine how much influence the intensity of uploading videos to self exixtence of members Pkuvidgram.The method used in this research was quantitative method with explanatory survey, researcher collected data using questionnaires. The location of this research is on the community Pkuvidgram (Pekanbaru Video Instagram). The number of samples for this research were 60 respondents to the census method is to take the whole subject in the population. To determine how much influence these two variables, the researchers used a simple linear regression analysis. As for the questionnaires data processing use Statistic Program Product of Service Solution (SPSS) version of Windows 16.Results of research on the influence of intensity uploading videos to self-exixtence of members Pkuvidgram, research shows that the correlation coefficient values obtained in this study is Y=27.649+1.829X 0.000 significance level smaller than α = 0.05. This means that there is the influence of intensity uploading videos to self-existence of members Pkuvidgram as much 44.2% which is in moderate category, known from the test results the coeefficient of determination, that means the members Pkuvidgram utilize social media of instagram to share the video in order to improve their own existence to the social environment.Keyword: intensity, uploading video, instagram, existence, pekanbaru video instagram